NGO Act as Potential-Policy-Developer Social-Vaccine-COVID-19 Epidemic-Model until Discovery-of-Medical-Vaccine: Achieved Green-Socio-Economic Welfare Science Technology Innovations - Chandra Datta, Subhas (Archives of Community Medicine and Public Health, 2020)
Introduction: The epidemic-COVID-19 spreads all around the world forming total change of human civilization, health, travel, socioeconomic, education, and clinical research. It has no targeted therapeutics, and effective treatment options, remain very limited. Though the middle-and upper-classes are able to manage, but the low-income-households, the marginalized in the cities, and groups like senior-citizens and street children as well as street-animals, are really suffering. So the Government of India as well as the whole world, wants to reorient for the COVID-19 crisis, by developing policy-initiative. Methods: Now it is focused on the young (students)-local-Non-Governmental-Organization (NGO) named “Burdwan-Green-Haunter and Students’-Goal”, take initiative or emphasis on different activates; social-awarenesscamp in different-ways, consume-nutritious-vegetables, clean-hands with soap, use-masks, maintain physical-orsocial-distance, avoid-touching eyes-nose-mouth, adopt strict-lockdown-measures, arrange blood-donation-camp, tree-plantation with conservation-biodiversity, day-celebration, and reduce-economic-activities to a minimum, distributing-rations to families in slums to providing cooked-meals to migrants to ensuring that senior-citizens have medicines, distributing-clothes, educational-materials also, and by taking some simple precautions, and nutritiousvegetables for improving immunity to human-disease-free-healthy-life with biodiversity-conservation. Results: All available evidence suggests that their different-human-resource-creating green-effective actively acts as a ‘Social-Vaccine-COVID-19 Epidemic-Models’ for the best of humanity to overcome COVID-19’s spread and protect us all. It is noted that NGOs are deeply rooted in local communities are best positioned to lead long-term-plans to stop COVID-19, and the NGOs are the closest to the community and will need to help for the most effective service right now. Conclusions: NGO will enrich their fund by public-donation as well as Government-grants, which will help to more activities in the communities around the world so that they are all better equipped to face any future COVID-19 outbreaks, and it will be one of the milestone events amidst many important changes in the past decade that have necessitated formulation of a new outlook and strategy for Science-Technology-Innovation-Policy (STIP), the future “NGO-Potential-Policy-Developer-Social-Vaccine-COVID-19-Epidemic-Models. Against-Corona-CrisisAchieved-Sustainable-Development-Socio-Economic-Welfare-Science-Technology-Innovations” by enriching community immunity or herd-immunity. STIP 2020 by way of its decentralized, bottom-up and inclusive-designprocess aims to strategize-priorities, sectoral-focus and methods of research and technology-development for larger green-socio-economic-welfare, based on the theme “Vision 2040” that would help policymakers, solving virusinduced economic-crisis globally also.